China’s Role In Confidence-Building Measures: Transforming the Pakistan–Afghanistan Security Dilemma into Cooperation - Maheen Kamran; Prof. Dr. Jamil Ahmad Chitrali (`, 2025)
This research examines China’s role as a facilitator and mediator in Pak–Afghan relations through the lens of Confidence-Building Measures (CBMs), particularly in addressing historical grievances, territorial disagreements, border violence, and mutual mistrust. The study explores the potential of China’s non-intervening approach, which balances economic interests with diplomatic engagement, to transform the security paradigm of Pak–Afghan rivalry into one of cooperation. Employing an analytical classification method, the research addresses the effectiveness of China-mediated CBMs in shifting bilateral relations from antagonism to partnership. The analysis considers political negotiations, integrated infrastructure projects, disarmament and reintegration programs, Taliban power constraints, sanctuaries, and security risks linked to the China–Pakistan Economic Corridor (CPEC). Drawing on an extensive literature review, the paper traces seventy years of Pakistan–Afghanistan relations, highlighting persistent issues such as the Durand Line dispute, transnational terrorism, transit trade, and water sharing. China’s mediation approach is framed around the concept of “developmental peace,” prioritizing bilateral economic fundamentals over political leverage, with megaprojects like CPEC and the Belt and Road Initiative (BRI) acting as facilitators. Adopting a qualitative research design, the study utilizes purposive sampling of 15 experts from China, Pakistan, and Afghanistan, with semi-structured interviews providing primary data to capture thematic insights into the effectiveness of Chinese mediation and its role in fostering sustainable peace-building mechanisms. Keywords: China’s Role, Confidence-Building Measures, Pakistan–Afghanistan Security Dilemma, Cooperation